A practical guide to clinical supervision in genetic counseling - Veach, Patricia McCarthy (New York, NY : Oxford University Press, 2023)
'A Practical Guide to Clinical Supervision in Genetic Counseling' provides a comprehensive overview of the clinical supervision of genetic counselling students. Chapters address key topics, such as relationship dynamics in clinical supervision, critical supervision processes, and common clinical supervision challenges. Activities at the end of each chapter help readers strengthen their skills and competencies, and are suitable for clinical supervisors of all experience levels.
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 13, 2023).
Keywords: Genetic counselors -- Supervision of; Genetic counselors -- Training of; Genetic counseling -- Management; Health and Wellbeing; Social services & welfare, criminology